Karakteristik dan Preferensi Pengguna Dalam Pemilihan Lokasi Parkir di Koridor Jalan Pemuda, Klaten - Marcellus Lendra Kusuma; Djoko Suwandono (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2019)
Pemuda road corridor is the main corridor in Klaten Regency which has function as Central Business District (CBD). The growth of an area led to the need for parking space also increased. The problem is that many parked carelessly vehicles that cause roadblocks and reduce the aesthetics of the city. Needs a parking area planning in accordance with the characteristics of the people there. The purpose of this study is to understand the characteristic and preferences of users in choosing of parking location on Pemuda road corridor Klaten Regency. Data collection in this study used primary data obtained from the questionnaire. The respondent's target in this research is all the people who park their vehicles in Pemuda road corridor, which is divided into four zones of location and three time zones; morning, noon and afternoon. The result is characteristics of the user in the morning is dominated by the purpose of visit is to work with a long time parking duration (> 4 hours), then in the noon is dominated by the purpose of visit is shopping with medium parking duration (1-2 hours), and shopping and recreation purposes with medium duration parking (1-2 hours) in the afternoon. Meanwhile the preference analysis puts the security variable to be the most important in choosing of parking location.